2012
DOI: 10.1142/s0219455412500289
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of Buckling of Advanced Fiber Composite Cylinders Under Axial Compression

Abstract: Advanced lightweight laminated composite shells are increasingly being used in modern aerospace structures, for enhancing their structural efficiency and performance. Such thin-walled structures are susceptible to buckling when subjected to static and dynamic compressive stresses. In this paper, details of a numerical (FEM) and an experimental study on buckling of carbon fiber reinforced plastics (CFRP) layered composite cylinders under displacement and load controlled static and dynamic axial compression are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…The results from the present ABAQUS models were compared with those from the experimental and numerical investigations reported by Priyadarsini, R. S et al (2012). It can be seen that the results of the present study, as shown in Figs.…”
Section: Validationmentioning
confidence: 67%
See 3 more Smart Citations
“…The results from the present ABAQUS models were compared with those from the experimental and numerical investigations reported by Priyadarsini, R. S et al (2012). It can be seen that the results of the present study, as shown in Figs.…”
Section: Validationmentioning
confidence: 67%
“…The shell's surface opens out to a horizontal plane. The imperfection in the cylinder was taken as the radial distance between the best-fit cylinder and the actual shell surface, as measured in the work of Priyadarsini et al (2012).…”
Section: Measurement Of Imperfectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subash et al [4] performed the buckling analysis of composite high pressure vessels and concluded that T-Sai Wu failure criteria can yield fairly good results with consistent accuracy for the composite pressure vessels. Priya darsini et al [5] performed the buckling analysis of cylinders with advanced composites. She said shown that the ultimate strength is affected by the method of loading (static, harmonic), the layup sequence, radius to thickness ratio and geometric imperfections.…”
Section: Introductionmentioning
confidence: 99%